2021
DOI: 10.18632/aging.203233
|View full text |Cite
|
Sign up to set email alerts
|

CircRNA FUT10 regulates the regenerative potential of aged skeletal muscle stem cells by targeting HOXA9

Abstract: Skeletal muscle is capable of repairing itself after injury to maintain the stability of its own tissue, but this ability declines with aging. Circular RNAs (circRNAs) are involved in cell aging. However, there is little research into their role and underlying mechanisms, especially in skeletal muscle stem cells (SkMSCs). In this study, we assessed circRNA FUT10 expression in aged and adult SkMSCs. We observed that circRNA FUT10 was upregulated in aged SkMSCs compared with that in adult SkMSCs. Furthermore, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…MiR-499-5p can regulate the development of skeletal muscle by regulating muscle gene expression through the NFATc1/MEF2C pathway [ 46 ]. In addition, studies have found that circRNA FUT10 can act as a sponge for miR-365a-3p to regulate the expression of HOXA9 and then regulate the senescence of skeletal muscle stem cells [ 47 ]; a novel circular RNA produced by FGFR2 gene by sponge miR-133a-5p and miR-29b-1-5p promotes myoblast proliferation and differentiation [ 12 ]; circMYBPC1 can promote myoblast differentiation by targeting MyHC and may promote skeletal muscle regeneration [ 48 ]. These findings suggest that circRNAs may play an intrinsic competition-regulated role during skeletal muscle development by interacting with miRNA.…”
Section: Discussionmentioning
confidence: 99%
“…MiR-499-5p can regulate the development of skeletal muscle by regulating muscle gene expression through the NFATc1/MEF2C pathway [ 46 ]. In addition, studies have found that circRNA FUT10 can act as a sponge for miR-365a-3p to regulate the expression of HOXA9 and then regulate the senescence of skeletal muscle stem cells [ 47 ]; a novel circular RNA produced by FGFR2 gene by sponge miR-133a-5p and miR-29b-1-5p promotes myoblast proliferation and differentiation [ 12 ]; circMYBPC1 can promote myoblast differentiation by targeting MyHC and may promote skeletal muscle regeneration [ 48 ]. These findings suggest that circRNAs may play an intrinsic competition-regulated role during skeletal muscle development by interacting with miRNA.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies using new methods would be required to reveal the regulation mechanism of IMF deposition. In recent years, advances in sequencing technology have revealed that long noncoding RNAs (lncRNAs) and circular RNAs (circRNAs) have emerged as important class of gene expression regulators that can regulate numerous biological processes, such as cancer progression, neurological disorders, cancer cell proliferation, and muscle contraction [ 4 , 5 , 6 , 7 , 8 , 9 , 10 ]. Studies had proven that several lncRNAs and circRNAs are involved in adipogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…The most significantly different circRNA was found to be circFUT10. The circFUT10 inhibited the differentiation of adult skeletal muscle stem cells by reducing the expression of MyoD and MyHC, while inhibition of circFUT10 promoted the differentiation of skeletal muscle stem cells in the aged group (Zhu et al, 2021). During myogenesis, circNfix acted as a sponge for miR‐204 to enhance MEF2C expression and promote myotube formation (Das et al, 2021).…”
Section: Research On Circrnas In Animal Husbandrymentioning
confidence: 99%